A Pilot Study to Assess Benefit of Atrial Rhythm Control after Cardiac Resynchronization Therapy and Atrioventricular Node Ablation. Issue 2 (27th November 2014) - SCHWARTZMAN, DAVID; HOUSEL, DEBRA; BAZAZ, RAVEEN; JAIN, SANDEEP; SABA, SAMIR; GORCSAN, JOHN; ADELSTEIN, EVAN
<x xml:space="preserve">Abstract</x> Background Atrial fibrillation (AF) is frequently comorbid in patients receiving cardiac resynchronization therapy (CRT), and suppression is typically difficult. Herein, we sought to understand the benefit of atrial rhythm control in the setting of ventricular rate and regularity control induced by atrioventricular node (AVN) ablation. Methods Fifty‐two patients with heart failure, persistent AF, left ventricular (LV) ejection fraction <35%, and left bundle branch block underwent cardiac resynchronization therapy (CRT) + AVN ablation, and were randomized to one of the following groups: (1) Atrial Rhythm Control (ARC); (2) AF. Patients were subsequently followed for up to 1 year. Results Similar numbers of patients in each group were lost to follow‐up or have withdrawn (ARC two; AF three). Rhythm control in four patients in the ARC group was inadequate. Among the remaining patients, the incidence of death (ARC=1, AF=2) or left ventricular assist device +/− transplantation (ARC=2, AF=1) were similar. Among the remaining patients (ARC 16, AF 19), at 1 year, there were no significant differences in CRT response rate, Minnesota Living with Heart Failure survey score, 6‐minute hall walk distance, ventricular tachyarrhythmia occurrence, or LV dimensions. A significantly higher hospital encounter rate among ARC patients was attributable to efforts to maintain uniform atrial rhythm. Conclusions In this pilot study, no incremental benefit for ARC was apparent. A larger study will be necessary to adequately examine these issues.